(untitled) (Biological Sciences - PJSIR, 2022)
Micro-nutrient formulations for agriculture purposes have been produced mounting copper, zinc, manganese and chromium on five-different frilled compositions. Release of elements was monitored by extracting the metals with ammonium citrate solution and estimating them by means of an atomic absorption spectrophotometer. The results show that release of copper can be controlled at a level of 1.4 to 4 ppm, that of zinc at 1.7 to 5.2 ppm, manganese at 1.8 to 8.6 ppm, while that of chromium at 0.02 to 0.3 ppm, by leachings, spread over a period of one hour to 10 days.